Standardization of the individual Zulliger test on non-clinical Italian population - Riccardo Caporale; Cettina Allone; Antonio Maccarone; Palmira Faraci; Giuseppe Craparo (Mediterranean Journal of Clinical Psychology)
Background: The Zulliger test (Z-test) is a projective technique, mainly used in the selection and evaluation of human resources, through a collective administration. It offers the possibility to investigate personality, assessing cognitive, affective, and interpersonal functioning, and the presence of psychopathology. The lack of normative data on the individual administration mode have encouraged this work. This is an extension of a previous work and includes statistical additional information on data obtained from the administration of the test on a non-clinical Italian population.